So for this, I will be using the substitution method. With the first equation, substitute y for (1/5x + 1) and from there solve for x:
![x+5((1)/(5)x+1)=-15\\x+x+5=-15\\2x+5=-15\\2x=-20\\x=-10](https://img.qammunity.org/2019/formulas/mathematics/high-school/osl5nbtjr003dafo27535lixta0qdonhh5.png)
Now that we have the value of x, substitute it into either equation to solve for y:
![-10+5y=-15\\5y=-5\\y=-1\\\\y=(1)/(5)*(-10)+1\\y=-2+1\\y=-1](https://img.qammunity.org/2019/formulas/mathematics/high-school/g6mzpudbfnstse8agvd46teqhoc8js500i.png)
The ordered pair that is the solution to this system of equations is (-10,-1).